Pneumococcal serotype-specific cut-offs based on antibody responses to pneumococcal polysaccharide vaccination in healthy adults - Park, Miguel A.; Jenkins, Sarah M.; Smith, Carin Y.; Pyle, Regan C.; Sacco, Keith A.; Ryu, Euijung; Hagan, John B.; Joshi, Avni Y.; Snyder, Melissa R.; Abraham, Roshini S. (Vaccine, 2021)
•IgG pneumococcal antibodies assessed in healthy pneumococcal-naïve adults.•Serotype-specific thresholds defined to pneumococcal polysaccharide vaccination.•The serotype-cutoffs is used for interpretation of pneumococcal antibody responses.•It may be useful in patients with humoral immunodeficiencies or other contexts. Antibody responses to pneumococcal polysaccharide vaccination are frequently used as a diagnostic tool for humoral immunodeficiencies, part of the larger collection of inborn errors of immunity. Currently, arbitrary criteria, such as a serotype specific titer of >/= 1.3 µg/mL is most often used as a cut-off for interpretation of pneumococcal antibody responses. The magnitude of the antibody response to each of the 23 serotypes in Pneumovax®, and serotype-specific cut-offs in healthy pneumococcal vaccine-naïve adults has not been previously characterized. IgG antibody concentrations were measured prospectively for 23 pneumococcal serotypes pre and 4–6 weeks post-Pneumovax® vaccination in 100 healthy adults, using a multiplex bead-based assay. Antibodies to 19 of 23 serotypes were informative for distinguishing subjects who responded to vaccination, and the serotype threshold was determined to be 9 of 19 serotypes, which characterized an antibody response to pneumococcal vaccination. While this study may facilitate classification of IgG serotype-specific antibody responses post-pneumococcal vaccination in adult patients undergoing diagnostic immunological evaluation for antibody immunodeficiencies or other relevant contexts, additional studies in healthy children and S. pneumoniae protein-conjugate-vaccinated healthy adults will need to be undertaken in the future.